The experience of approbation and empirical substantiation of the ecopsychological model of subjectivity development in educational practice - Irina V. Plaksina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paperpresents a brief summary of the results of theoretical approbation and empirical substantiation of V.I. Panovsecopsychological model of subjectivity development, obtained during the 20162022 studies carried out on samples of students (N=897), students of the Pedagogical Institute (N=379) and teachers of schools in Vladimir (N=196). The choice of the model is due to the need to solve the central task of educational practice stated by the Federal State Educational Standard at all levels - the development of students ability to be a subject of educational activity. The ecopsychological model of subjectivity development, invariant to the subject content, allows us to consider the gradual subjectivity development at the theoretical and empirical levels in the context of ecopsychological interactions in the "student teacher/educational environment" system. The analysis and comparison of the results obtained in different years on different samples revealed a number of patterns of development of the subject of educational, educational and professional activity: violation of the process of transferring components of educational activity from teacher to student, the return of a third of 11th grade students to reproductive methods of activity (low stages of subjectivity), the deficit of subject-generating interactions in educational environments in assessment of students, etc. The results obtained on student samples are characteristic of the traditional method of training future teachers, focused on the transfer of knowledge in the subject area. The experimental verification of the ecopsychological model on a sample of teachers implementing the regional innovative project "Organizational and psychological-pedagogical conditions for subjectivity development of participants in the educational process" confirmed the validity of the choice of the ecopsychological model of the development of the subject of pedagogical activity. Theoretical substantiation and empirical verification of the ideas of the ecopsychological approach allows us to assert that the ecopsychological model of the formation of subjectivity by V.I. Panov objectifies the realities of educational practice, differentiates ideas about interactions in the "student educational environment" system, allows us to identify the degree of orientation to the psychological patterns of student development, and serves as the basis for the development of a psychodidactic model of learning in accordance with ecopsychological stages of subjectivity development.